(untitled) (Public Sector Economics - submission site, 2022)
This paper evaluates the relationship between public policy reforms and productivity, investment, employment and per capita income for OECD and non-OECD countries. More competition-friendly product market regulations are associated with improved economic outcomes: lower barriers to foreign trade and investment go in tandem with greater multi-factor productivity (MFP), and lower barriers to entry and less pervasive state control over the business sector with larger capital stock and increased employment rate. More flexible labour market regulations are found to go hand in hand with higher employment rates whereas no robust link between labour market regulations and MFP and capital deepening can be established. The findings also suggest that the quality of institutions is fundamental for economic outcomes. Finally, the paper shows that countries at different levels of economic development face different policy effects and that some policy reforms interact with each other by attenuating and amplifying each others’ economic impacts.